Stillbirth and neonatal mortality in a subsequent pregnancy following stillbirth: a population-based cohort study - Janna W. Nijkamp; Anita C. J. Ravelli; Henk Groen; Jan Jaap H. M. Erwich; Ben Willem J. Mol (BMC, 2022)
Abstract Background A history of stillbirth is a risk factor for recurrent fetal death in a subsequent pregnancy. Reported risks of recurrent fetal death are often not stratified by gestational age. In subsequent pregnancies increased rates of medical interventions are reported without evidence of perinatal benefit. The aim of this study was to estimate gestational-age specific risks of recurrent stillbirth and to evaluate the effect of obstetrical management on perinatal outcome after previous stillbirth. Methods A retrospective cohort study in the Netherlands was designed that included 252.827 women with two consecutive singleton pregnancies (1st and 2nd delivery) between 1999 and 2007. Data was obtained from the national Perinatal Registry and analyzed for pregnancy outcomes. Fetal deaths associated with a congenital anomaly were excluded. The primary outcome was the occurrence of stillbirth in the second pregnancy stratified by gestational age. Secondary outcome was the influence of obstetrical management on perinatal outcome in a subsequent pregnancy. Results Of 252.827 first pregnancies, 2.058 pregnancies ended in a stillbirth (8.1 per 1000). After adjusting for confounding factors, women with a prior stillbirth have a two-fold higher risk of recurrence (aOR 1.96, 95% CI 1.07-3.60) compared to women with a live birth in their first pregnancy. The highest risk of recurrence occurred in the group of women with a stillbirth in early gestation between 22 and 28 weeks of gestation (a OR 2.25, 95% CI 0.62-8.15), while after 32 weeks the risk decreased. The risk of neonatal death after 34 weeks of gestation is higher in women with a history of stillbirth (aOR 6.48, 95% CI 2.61-16.1) and the risk of neonatal death increases with expectant obstetric management (aOR 10.0, 95% CI 2.43-41.1). Conclusions A history of stillbirth remains an important risk for recurrent stillbirth especially in early gestation (22-28 weeks). Women with a previous stillbirth should be counselled for elective induction in the subsequent pregnancy at 37-38 weeks of gestation to decrease the risk of perinatal death.